Model Mekanisme FinTech untuk Inovasi Teknologi pada Industri Keuangan dan Perbankan Indonesia - Mercurius Broto Legowo; Steph Subanidja; Fangky Antoneus Sorongan (Prosiding SISFOTEK, 2020)
FinTech, a word derived from a combination of "Financial" and "Technology”. Nowadays, this term refers to a new business in the Indonesian financial and banking industry, a technological innovation that is attracting public attention. The purpose of this study is to develop a FinTech mechanism model for technological innovation in the Indonesian Financial and Banking Industry. Problems arise in how to develop the FinTech mechanism model that influenced by business drivers factors, which in turn has an impact on technology innovations that developed. In this case study, the research used is mixed-method, which is a method that combines qualitative and quantitative methods. Qualitative research data were collected using the literature study, in-depth interviews, and Focus Group Discussions with related parties. Data survey using a questionnaire conducted for quantitative research, where the data was processed using smartPLS software. The results of this study produce a theoretical framework, which is the basis of the conceptual framework and empirical model of this research. The results of empirical tests on this model show that the FinTech mechanism has a role in mediating business drivers factors towards technology innovations developed in the Indonesian Financial and Banking Industry. The contribution of this research can provide insight and understanding for researchers and practitioners who want to develop business models related to FinTech in more depth.